Primary biliary cirrhosis and Sjogren's syndrome: Autoimmune epithelitis - Selmi, Carlo (2011)
Primary biliary cirrhosis (PBC) has been often coined a model autoimmune disease based on the homogeneity amongst patients, the frequency and similarity of antimitochondrial antibodies, including the highly directed immune response to pyruvate dehydrogenase (PDC-E2). A significant number of patients with PBC suffer from sicca and amongst these, there are patients who also have classic Sjogren's syndrome. Indeed, both PBC and Sjogren's syndrome are characterized by inflammation of target epithelial elements. Both diseases can be considered on the basis of a number of other related clinical aspects, including proposed unique apoptotic features of the target tissue, the role of secretory IgA, and the frequency with which both diseases overlap with each other. Indeed, PBC may be considered a Sjogren's syndrome of the liver, whereas Sjogren's syndrome can be equally discussed as PBC of the salivary glands. Dissection of the genetic predispositions for both diseases and especially the molecular basis of effector mechanisms, will become critical elements in developing new therapies.